Fe-based catalytic modification of a birch sawdust-based carbon structure: The effect of process parameters on the final product using an experimental design - Henna Lempiäinen; Davide Bergna; Anne Heponiemi; Tao Hu; Glaydson S. dos Reis; Rafal Sliz; Ulla Lassi (Carbon Trends)
Biomass waste-based, graphite-like material is an interesting alternative to fossil carbons in, for example, battery solutions. The aim was to produce carbon with a graphite-like structure from birch waste through catalytic modification with iron nitrate at relatively low temperatures. The study highlighted the effects of the Fe/birch mass ratio (0–20 mg Fe/g birch), heating temperature (750–900 °C), holding time (1–6 h), and heating rate (3–10 °C/min) on the carbon. The influence of each factor was demonstrated using a design of experiments (DoE) approach. Changes in yield, chemical composition, morphology, specific surface area, total pore volume, pore size distribution, particle size, tapped density, and conductivity were analyzed. The results showed that temperature affected the chemical content, yield, and conductivity. Iron-impregnation affected the structure of birch by modifying its total pore volume, tapped density, ID/IG value, and conductivity. The heating rate and holding time had relatively little effect. The highest conductivity (7.23 S/cm) was obtained when impregnated birch was pyrolyzed at the maximum temperature, holding time, and heating rate. However, the best graphitization result (ID/IG 0.98) was obtained when iron-impregnated birch was heated for 6 h at 750 °C at a heating rate of 3 °C/min.